Upaya Meningkatkan Imunitas Keluarga di Masa PPKM Mikro Melalui Konsumsi Gizi Seimbang - Rokhmah, Dewi; Handayani, Septi; Pujiati, Rahayu Sri; Khoiron, Khoiron (Jurnal Pengabdian Pada Masyarakat, 2022)
EFFORTS TO İNCREASE FAMİLY IMMUNİTY İN THE MİCRO PPKM PERİOD THROUGH BALANCED NUTRİTİON CONSUMPTİON. Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been previously identified in humans. After the emergence of COVID-19, the government began to implement policies in prevention and control of COVID-19, such as the establishment of a Task Force for the Acceleration of Handling COVID-19, promoting the implementation of health protocols, Large Scale Social Restrictions, and Policy to Enforcement of Community Activity Restrictions Micro, and COVID-19 Vaccination. To prevent COVID-19, it can be done by increasing immunity through the consumption of balanced nutrition. Based on results of the analysis conducted, the majority of people in Juglangan Village have not implemented a balanced nutritional consumption pattern, so counseling is needed to give information to participants and then apply a balanced nutritional pattern. Extension activities are carried out using the lecture method with Power Point media and using the Zoom meeting application. In addition, pre-test and post-test were also given to measure participants’ understanding of the material. During the activity, participants were very enthusiastic in understanding the material and discussions. This is also shown by the satisfactory results of the pre-test and post-test where there is an increase in the knowledge gained by the participants after the counseling activities.